PENGARUH KONSENTERASI LARUTAN NaOH TERHADAP KUAT TEKAN MORTAR GEOPOLIMER BATU NAPAL - Fernando; Vike Itteridi; Masagus Taswin (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
: As the times develop portland cement became a very important material and it widely used to build various infrastrcture. However the process of making cement would cause a big problem which is releasing carbon dioxide (Co2) into the atmosphere freely which resulting in the depletion of the ozone layer. Geopolymer mortar was a mixture of which the basic material did not use the portland cement as a binder. Did to find out the effect of the use of geopolymer marls a study was conducted using experimental methods. The purpose of this study was to determine the effect of NaOH contentration strength of marl geopolymer mortar. Cube specimens measurring 5 x 5 x 5 cm3 with molarity variations 8M,10M, 12M, 14M, and 16M as many as 75 specimens. Mortar curing by drying it at room temperture, at ages 3, 7, 14, 21, and 28 day. From the results of the research, the maximum density of geopolymer mortar was obtained at the age of 28 day using a 16M activator ratio of 2,30 grams, and the maximum compressiv strenght value of geopolymer at 28 days using a 16 M activator ratio was 8,13 Mpa. It could be conclouded that the higher molarity was used in the mixture then the mor OH- was presesnt in the mixture so that the process the bind ing would go much faster.